Fault-tolerance in metric dimension of boron nanotubes lattices - Hussain, Zafar; Munir, Muhammad Mobeen (Frontiers in Computational Neuroscience, 2023)
. Concept of resolving set and metric basis has enjoyed a lot of success because of multi-purpose applications both in computer and mathematical sciences. A system in which failure of any single unit, another chain of units not containing the faulty unit can replace the originally used chain is called fault-tolerant self-stable system. Recent research reveal that the problem of finding metric dimension is NPhard and problem of computing the exact values of fault tolerant metric dimension seems to be even harder although some bounds can be computed rather easily. In the present article we compute closed formulas for the fault-tolerant metric dimension two types of Boron nanotubes, namely truiangular and alpha. We come to a conclusion that both tubes have constant fault tolerance metric dimension 4.